Injection Drug Use and Hepatitis C as Risk Factors for Mortality in HIV-Infected Individuals: The Antiretroviral Therapy Cohort Collaboration. - May, Margaret T; Justice, Amy C; Birnie, Kate; Ingle, Suzanne M; Smit, Colette; Smith, Colette; Neau, Didier; Guiguet, Marguerite; Schwarze-Zander, Carolynne; Moreno, Santiago; Guest, Jodie L; Monforte, Antonella dʼArminio; et al. (Journal of acquired immune deficiency syndromes (1999), 2015)
HIV-infected individuals with a history of transmission through injection drug use (IDU) have poorer survival than other risk groups. The extent to which higher rates of hepatitis C (HCV) infection in IDU explain survival differences is unclear.
Keywords: Adolescent; Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Cohort Studies; Female; Hepatitis C; HIV Infections; Humans; Male; Middle Aged; Risk Factors; Substance Abuse, Intravenous; Survival Analysis; Treatment Outcome; Viral Load; Young Adult